PERAN GURU DALAM GERAKAN LITERASI DI SEKOLAH DASAR - Yohanes Wendelinus Dasor; Honorita Mina; Eliterius Sennen (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2021)
Literacy is a comprehensive process that involves knowledge, culture, and intelligence to develop new knowledge and add deep insights. According to the results of an international survey, elementary school students throughout Indonesia have literacy skills at the lowest level. So to develop students' literacy skills, here it is necessary to have a teacher's role to build students in a literacy culture. There are several roles of teachers in the literacy movement in schools, namely teachers as role models, teachers as motivators, teachers as facilitators and creators, providing facilities and infrastructure, and providing rewards and punishments. Some of these roles ensure that they can increase the literacy culture among students. Without the role of the teacher, it is impossible for a literacy culture to be embedded in students.